Hubungan Vaksinasi Rotavirus dengan Kejadian Diare pada Anak Usia 6-24 Bulan di Kota Denpasar - Widiantari, Ni Made; Cempaka, Putu Mas Vina Paramitha; Nesa, Ni Nyoman Metriani; Karyana, I Putu Gede; Wati, Ketut Dewi Kumara (E-Jurnal Medika Udayana; Vol 11 No 2 (2022): E-Jurnal Medika Udayana, 2022)
Diarrhea constantly becomes an issue of health because of its high mortality and morbidity. Rotavirus infection is known as the predominant cause of acute diarrhea with severe dehydration and hospitalized diarrhea among children less than five years of age. Therefore, rotavirus vaccination is supposed to provide protective effect against the diarrhea cases. The study was implemented to prove the association between rotavirus vaccination and the diarrhea cases among children 6-24 months of age in Denpasar City. The study used an observation cross-sectional analytic design located at private pediatric clinic in Denpasar City and Puskesmas III Denpasar Utara from January to June 2020. The subjects selected by consecutive sampling technique were 104 children 24-36 months of age who divided into vaccinated and unvaccinated groups. The diarrhea cases were measured retrospectively from 6-24 months of age. The study data were derived through questionnaires, processed and analyzed through chi-square and logistic regression test on SPSS. In this study, the percentage of diarrhea cases in the vaccinated group (15,4%) was smaller than the unvaccinated group (36,5%). The statistical test showed PR = 0,42, 95% CI = 0,271-0,654, and p value = 0,001 (p<0,05) which means that rotavirus vaccination was significantly associated with the diarrhea cases and acts as a protective factor. Keywords : Children, Diarrhea, Rotavirus, Vaccination